Heredity under the microscope chromosomes and the study of the human genome - Chadarevian, Soraya de (The University of Chicago Press, 2020)
By focusing on chromosomes, Heredity under the Microscope offers a new history of postwar human genetics. Today chromosomes are understood as macromolecular assemblies and are analyzed with a variety of molecular techniques. Yet for much of the twentieth century, researchers studied chromosomes by looking through a microscope. Unlike any other technique, chromosome analysis offered a direct glimpse of the complete human genome, opening up seemingly endless possibilities for observation and intervention. Critics, however, countered that visual evidence was not enough and pointed to the need to understand the molecular mechanisms. Telling this history in full for the first time, Soraya de Chadarevian argues that the often bewildering variety of observations made under the microscope were central to the study of human genetics. Making space for microscope-based practices alongside molecular approaches, de Chadarevian analyzes the close connections between genetics and an array of scientific, medical, ethical, legal, and policy concerns in the atomic age. By exploring the visual evidence provided by chromosome research in the context of postwar biology and medicine, Heredity under the Microscope sheds new light on the cultural history of the human genome.